BONUM COMMUNE SEBAGAI SASARAN GERAKAN BURUH MENURUT AJARAN SOSIAL GEREJA - Nadeak, Largus (Universitas Katolik Santo Thomas Sumatera Utara, 2002)
The labourersâ numbers have increased in line with the development of industrialization. But this development did not parallel to the appreciation on the fruit of the labourersâ work. Since long labourers become the object of work and violence. Church social teaching has anticipated labourersâ problem since the year 1891 through the Encyclical letter âRerum Novarumâ. Itâs main point is that man is homo laborans. When human put in on the job, they will fulfil their needs and also form their self-integrity. Therefore menâs/womenâs job must be paid in a proper payment in accordance to the fruit of their work and ability of enterprise. Communion secure and prosperous should be the aim of this movement. Bonum Commune gives assurance to the rights of every human as individual, and right of every human in the certain social communities. The church social teaching should be the light on the labourersâ movement to make a change in an injustice toward bonum commune.